Feasibility of immunotherapy in cancer patients with persistent or past hepatitis B or C virus infection. Issue 5 (22nd April 2022) - Nakabori, Tasuku; Abe, Yutaro; Higashi, Sena; Hirao, Takeru; Kawamoto, Yasuharu; Maeda, Shingo; Daiku, Kazuma; Urabe, Makiko; Kai, Yugo; Takada, Ryoji; Yamai, Takuo; Ikezawa, Kenji; et al.
Abstract: Background and Aim: Immune checkpoint inhibitors (ICIs) can cause immune‐related adverse events in the liver. The risk of exacerbating liver injury is of concern in patients infected with hepatitis B virus (HBV) or hepatitis C virus (HCV), as immunotherapy can damage liver function because of the immune response against viral antigens. We assessed the feasibility of immunotherapy in HBV‐ or HCV‐infected patients. Methods: This retrospective study included 266 patients with persistent or past HBV infection, 26 patients seropositive for anti‐HCV, and 820 patients with negative viral markers for HBV and HCV, who were treated with ICIs. ICI‐induced liver injury and changes in virological markers were analyzed. Results: The occurrence rates of ICI‐induced liver injury in the HBsAg‐positive, anti‐HBc‐positive/anti‐HBs‐positive, and anti‐HBc‐positive/anti‐HBs‐negative groups were 12.5, 21.6, and 19.1%, respectively, which were comparable with those of the negative for HBV‐ and HCV‐related markers group (20.9%). The frequency of any grade ICI‐induced liver injury was different among the HCV RNA‐positive (3/5; 60.0%), anti‐HCV‐positive/HCV RNA‐negative (2/21; 9.5%), and negative for HBV‐ and HCV‐related markers (171/820; 20.9%) groups ( P  = 0.045), with no significant difference in grade ≥2 ICI‐induced liver injury. In patients with persistent infection, neither serum HBV DNA, HBsAg, nor HCV RNA level changed significantly during ICI treatment. One of five treatment‐naïve HCV‐infected patients required interruption of ICI treatment due to virus‐related liver injury. Conclusion: Immunotherapy is feasible for most cancer patients with chronic HBV or HCV infection; however, liver function and virological markers should be carefully monitored in treatment‐naïve patients, especially those with HCV infection, during ICI treatment. Abstract : There were no significant differences in the frequency of any grade or grade ≥2 immune checkpoint inhibitor (ICI)‐induced liver injury in cancer patients with persistent or past hepatitis B virus (HBV) infection. No significant difference was observed in the frequency of grade ≥2 ICI‐induced liver injury in cancer patients positive for hepatitis C virus (HCV)‐related markers, though HCV‐RNA positive patients had a higher frequency of any grade ICI‐induced liver injury to occur. Therefore, immunotherapy is feasible for most chronic HBV or HCV cancer patients; however, in the treatment‐naïve patients, especially those with HCV infection, liver function and virological markers should be monitored carefully during ICI treatment.